In Silico Analysis of Putative Sugar Transporter Genes in Aspergillus niger Using Phylogeny and Comparative Transcriptomics - Peng, Mao; Aguilar-Pontes, Maria V.; de Vries, Ronald P.; Mäkelä, Miia R. (Frontiers in Microbiology, 2018)
Aspergillus niger is one of the most widely used fungi to study the conversion of the lignocellulosic feedstocks into fermentable sugars. Understanding the sugar uptake system of A. niger is essential to improve the efficiency of the process of fungal plant biomass degradation. In this study, we report a comprehensive characterization of the sugar transportome of A. niger by combining phylogenetic and comparative transcriptomic analyses. We identified 86 putative sugar transporter genes based on a conserved protein domain search. All these candidates were then classified into 9 subfamilies and their functional motifs and possible sugar-specificity were annotated according to phylogenetic analysis and literature mining. Furthermore, we comparatively analyzed the sugar transporter gene expression on a large set of fungal growth conditions including mono-, di- and polysaccharides, and mutants of transcriptional regulators. This revealed that transporter genes from the same phylogenetic clade displayed very diverse expression patterns and were regulated by different transcriptional factors. The genome-wide study of sugar transporters of A. niger provides new insights into the mechanisms underlying an extremely flexible metabolism and high nutritional versatility of A. niger and will facilitate further biochemical characterization and industrial applications of these candidate sugar transporters.